Fundamental principles of occupational health and safety - Alli, B. O. (Benjamin O.) (International Labour Office, 2001)
Covers the fundamental principles of occupational health and safety, based on the ILO?s philosophy of prevention and protection, which stems from the organization?s mandate in the field of occupational health and safety. Serves as a guide for the development of occupational health and safety policies and programmes.